Committed to the promotion of sustainable agricultural development and prosperity of rural communities in Jamaica - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The Jamaican economy continued to experience major setbacks in several sectors during 2001. The agriculture sector continues to be challenged by globalization and trade liberalization, particularly the erosion of preferential markets for the traditional export commodities, sugar and banana, advances in information technology and the opening up of the domestic market to competition within the World Trade Organization (WTO), Free Trade Area of the Americas (FTAA) and Caribbean Single Market and Economy (CSME) processes.